2005
DOI: 10.1159/000082999
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Gender on Baseline Features and Clinical Outcomes among 17,370 Patients with Confirmed Ischaemic Stroke in the International Stroke Trial

Abstract: Aim: We sought to determine whether there were differences between men and women with acute stroke in their baseline characteristics and outcome in a large cohort of patients randomized in the International Stroke Trial (IST). Methods: Of the 19,435 patients randomized in the IST, 17,370 had an ischemic stroke confirmed by CT scan or autopsy (8,003 female and 9,367 male). In males and females, we compared baseline characteristics (age, frequency of atrial fibrillation, pre-stroke administration of aspirin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

15
197
2
7

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(221 citation statements)
references
References 36 publications
15
197
2
7
Order By: Relevance
“…Similarly, all 3 models for stroke incidence among patients with arrhythmias indicated that women were at higher risk, concordant with the literature 65, 66, 67. Conversely, our finding that all 4 models estimate lower risk of death after ischemic stroke for women than otherwise similar men was surprising given the inconsistency of the literature, which has frequently reported worse prognoses in women (particularly in populations untreated with thrombolysis) 17, 68, 69, 70. Finally, it is notable that about half of the models predicting stroke in a population sample were sex stratified (thereby allowing the effects of risk factors to vary among men and women), in keeping with evidence that sex modifies the effect of some risk factors on stroke risk 20, 71…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, all 3 models for stroke incidence among patients with arrhythmias indicated that women were at higher risk, concordant with the literature 65, 66, 67. Conversely, our finding that all 4 models estimate lower risk of death after ischemic stroke for women than otherwise similar men was surprising given the inconsistency of the literature, which has frequently reported worse prognoses in women (particularly in populations untreated with thrombolysis) 17, 68, 69, 70. Finally, it is notable that about half of the models predicting stroke in a population sample were sex stratified (thereby allowing the effects of risk factors to vary among men and women), in keeping with evidence that sex modifies the effect of some risk factors on stroke risk 20, 71…”
Section: Discussionsupporting
confidence: 86%
“…GWTG‐Stroke, when linked to administrative data, provides a unique opportunity to systematically characterize patients’ linguistic needs, understand how they are met, and identify their influence on patients’ care and outcomes. Second, our study results expand our knowledge of racial and socioeconomic factors associated with stroke care disparities, reinforcing that we need to better understand and address the social determinants of stroke care and outcomes 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51. The Office of Minority Health provides a framework for healthcare systems to meet patient linguistic needs through the National Standards for Culturally and Linguistically Appropriate Services in Health Care 52.…”
Section: Discussionmentioning
confidence: 61%
“…Clinical studies showed that males experience higher risk of stroke than females [162][163][164]. In rodent stroke, premenopausal females exhibit smaller infarct size than age-matched males [88,[165][166][167][168].…”
Section: Sex-associated Modulation Of Mononuclear Phagocytesmentioning
confidence: 99%
“…However, the risk of stroke is increased as females age [169][170][171][172]. More severe strokes and poorer recovery was observed in elderly women and aged rodents, regardless of the sex [162][163][164][173][174][175][176]. A primary ovarian hormone, estrogen has been associated with the sex difference in ischemic stroke as treatment of estrogen in the male or ovariectomized animals reduced infarct and neuronal death following ischemia [177][178][179][180].…”
Section: Sex-associated Modulation Of Mononuclear Phagocytesmentioning
confidence: 99%